Spatial study of the implementation of ivermectin, diethylcarbamazine citrate, and albendazole in an urban area - Nafilata, Ikrimah; Supali, Taniawati; Wahyono, Tri Yunis Miko; Prihartono, Nurhayati Adnan; Hikmah, Kholisotul; Devi, Yuli Puspita (Intelektual Pustaka Media Utama, 2025)
Studies on lymphatic filariasis (LF) in Indonesia have mostly focused on the disease determinants with limited focus on spatial-based and the determinants of implementing ivermectin, diethylcarbamazine citrate, and albendazole (IDA). This study aimed to identify the causes of program failure. A cross-sectional survey was conducted from November to December 2022 in nine urban villages with high endemic records and one sentinel village in Pekalongan City, Central Java, Indonesia. The analysis using Quantum Geographical Information System (QGIS) and Pearson correlation. Slum settlements were linked to the presence of open sewers (p=0.000; r=0.974) and overcrowding (p=0.033; r=0.672), while the first round of IDA medication adherence correlated with knowledge of medication (p=0.054; r=-0.623) and willingness to take the medication in the second round (p=0.051, r=0.603). Adverse effects of the treatment are strongly correlated with drug boredom from taking medication (p=0.003; r=0.828) and assistance from health workers (p=0.027; r=0.791). We identified gaps in slum settlements, open sewers, overcrowding and medication adherence, including low knowledge of medication, unwillingness to take second-round medication, adverse effects, and boredom with taking medication. We recommend effective strategies by engaging health education between health workers, local leaders, and private sectors as key to ensuring elimination program.